LEADERSHIP PRACTICES AND TEACHER DEVELOPMENT IN LBPP LIA MERCU BUANA - Wulandari, Respati; Prasetya, Agustian Budi (Journal of Business Strategy and Execution, 2014)
Leadership plays an important role in the organization. The role of leaders in any organization is very dominant in generating employee’s development. The company's goal will be difficult to achieve if the employee does not explored its potential as fully as possible or in placing the company among potential employees. Employee’s development plays an important role in organization. This is the part when employees know their personal and professional development in their job. Employee development is a key contributor to a business strategy based on developing intellectual capital, helps develop managerial talent, and allows employee to take responsibility for their careers. The purpose of this research is to determine the leadership factors that effect and predict teacher’s development in LBPP LIA Universitas Mercu Buana. After finding the result of this research, LIA UMB leader and management could utilize the information to enhance teacher’s development in LIA UMB. This research is supported by qualitative and quantitative research and could be concluded that leadership factors which is encourage, respect, responsible, discipline, supportive and communicative are significantly related to employee development. Based on the research, it can be found which leadership factors that predict teacher’s development in LIA UMB.